Evaluative practices of High School Mathematics teachers: the case of the Education, Science and Technology Federal Institute of Ceara, Caninde Campus (Research, Society and Development, 2020)
The discussion on the evaluative practices and instruments used to assess students' learning in the school environment can contribute to a reframing of the teaching work. As such, the present article has the general objective of understanding the evaluative practices of Mathematics teachers who worked in the High School of a Federal Institution during the 2019.2 semester. Specifically, analyzing the evaluation proposal of the official documents, as well as their alignment with the evaluative practices of these teachers and identifying the evaluative instruments used by them. The theoretical framework was substantiated by Hoffmann (1997), Depresbiteris (2000), Luckesi (2011), Libâneo (2013, 2014), Vasconcellos (2014), among others. The approach was qualitative and presented characteristics of the case study and the documentary research. For data collecting, the instrument used was a questionnaire with essay questions and for its analysis, Minayo's (2016) guidelines were followed. The results showed that evaluative practices are characterized as traditional, with little reference to official guidelines, exams being the main evaluative instrument. In this sense, there is an urgent need for a thoughtful look from teachers at the objectives to be achieved, as well as the other teaching elements (content, teacher-student relationship, methodology and evaluation), with planning not focused on just one of them (evaluation).